2018
DOI: 10.3892/mmr.2018.9287
|View full text |Cite
|
Sign up to set email alerts
|

miR‑200b‑3p inhibits proliferation and induces apoptosis in colorectal cancer by targeting Wnt1

Abstract: MicroRNA (miR)-200b-3p is downregulated in multiple human cancer types. Wnt signaling serves a role in human colorectal cancer (CRC). The present study aimed to examine the effect of miR-200b-3p on human CRC and its potential association with Wnt signaling. The Cell Counting Kit-8 (CCK-8) was employed to assess cell viability. A flow cytometric assay was conducted to examine cell proliferation and apoptosis. The regulation model of miR-200b-3p and Wnt1 was assessed by a luciferase reporter assay. A commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The discovery of the function of lncRNA-PVT1 was also demonstrated by inhibiting the expression of lncRNA-PVT1 in glioma cells. In recent years, a number of studies have confirmed miR-200 family expression disorders in a variety of tumor tissues, wherein they participate in tumor cell proliferation, migration, and invasion and the regulation of biological processes (8)(9)(10)29). Although miR-200a has been demonstrated to target many protein-coding genes, the present study suggested that miR-200a also targets lncRNA-PVT1.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The discovery of the function of lncRNA-PVT1 was also demonstrated by inhibiting the expression of lncRNA-PVT1 in glioma cells. In recent years, a number of studies have confirmed miR-200 family expression disorders in a variety of tumor tissues, wherein they participate in tumor cell proliferation, migration, and invasion and the regulation of biological processes (8)(9)(10)29). Although miR-200a has been demonstrated to target many protein-coding genes, the present study suggested that miR-200a also targets lncRNA-PVT1.…”
Section: Discussionmentioning
confidence: 51%
“…However, the high expression of lncRNA-PVT1 in tumor cells remains unclear. In recent years, numerous studies have confirmed that miR-200 family expression disorders exist in multiple tumor tissues and participate in the regulation of biological characteristics such as tumor cell proliferation, migration and invasion (8)(9)(10). The miR-200 family inhibits epithelial-mesenchymal transition (EMT) by directly targeting the expression of zinc finger E-box binding homeobox 1/2 (ZEB1/ZEB2) and then inhibits the migration and invasion of tumor cells (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-200b-3p belongs to a miR-200 miRNA family, known to be associated with a wide range of human cancers [ 29 ], and has been mainly reported as a tumor suppressor inhibiting cell growth and motility of breast cancer cells [ 30 ], suppressing metastasis in renal cell carcinoma and breast cancer [ 31 , 32 ], inhibiting proliferation, cell cycle and inducing apoptosis in gastric and colorectal cancers [ 33 , 34 ]. Nevertheless, the role of miR-200b-3p in cancer remains controversial, since studies showing the opposite effects on cancer cells exist [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of Wnt1 by WIF-1 or its antibody induced a significant apoptosis of human CRC cells containing mutations of APC, CTNNB1, and AXIN2 (79). Moreover, the ectopic expression of microRNA (miR)-200b-3p and miR-185 could significantly inhibit the proliferation and induce the apoptosis of CRC cells by targeting the canonical Wnt1/β-catenin signaling (80,81). However, researches on the Wnt1 expression in human CRC tissues have yielded some conflicting results that the decrease or the increase of Wnt1 expression was detected in CRC tissues compared with normal colorectal mucosa (25,27), and a study even found that the expression level of Wnt1 was decreased in human CRC tissues and CRC mice, whereas Wnt1 knockdown could still dramatically decrease the cell migration and the invasion of human CRC cells, and β-catenin expression was also enhanced in the tumors, indicating that Wnt1 expression could be regulated by more complicated mechanisms during CRC tumorigenesis (82).…”
Section: Wnt16mentioning
confidence: 99%